ChemInform Abstract: Direct Allylation of in situ Generated Aldehyde Acyl Anions by Synergistic NHC and Palladium Catalysis. Issue 51 (23rd December 2014) - Ahire, Milind M.; Mhaske, Santosh B.
Abstract Starting from easily accessible allylic carbonates and aldehydes, an efficient access to β, γ‐unsaturated ketones under mild reaction conditions is provided.